EVALUASI DAN PERANCANGAN USER EXPERIENCE PADA APLIKASI COVE MENGGUNAKAN UX HONEYCOMB - Sejati, Wiyar Wilujengning; Sibagariang, Efifania; Setiawan, Hermawan (Computer Based Information System Journal, 2024)
This research evaluates the Cove residential rental application using the Honeycomb UX model to improve user experience. Cove provides a residential rental service application in the form of boarding houses. Although the Cove app is available on various platforms, user ratings show some shortcomings. Through a literature review and UX assessment with 15 respondents, this study identified problems in seven important aspects of UX: useful, usable, findable, credible, accessible, desirable, and valuable. After design improvements that included the direct booking feature, user account system, property recommendation, chatbot feature, property rating system, and price transparency, the evaluation results showed a significant increase in user satisfaction, with the average UX score increasing from 3.63 to 4.56. These findings confirm that design improvements based on Honeycomb's UX model can improve overall user satisfaction and experience.